Altruism and evolutionary pahway. A review on the evolution of altruistic behaviour - Bernardes de Moraes, Thiago Perez; dos Santos Millani, Felipe (Nómadas. Critical Journal of Social and Juridical Sciences, 2015)
Since the brave attempts to bring Biology to the center of the social sciences discourse, by Edward Wilson and Richard Dawkins with their books Sociobiology and The Selfish Gene, more than forty years ago, Biology has gained recognition as one of the, if not the, main area in the search for human behavior understanding. Disciplines such as behavioral genetics, cognitive neuroscience, and evolutionary psychology among others have been brought to the center of the spectacle in the quest for the understanding of the mind and the influence of those areas is growing every day. Within this perspective this article brings attention to how the problem of understanding human altruism could be better comprehended with the addition of the information brought by the biological disciplines involved in the understanding of human behavior.